Effect of resistance training on muscle strength and rate of force development in healthy older adults: A systematic review and meta-analysis - Guizelini, Pedrode Camargo [UNESP]; de Aguiar, Rafael Alves; Denadai, Benedito Sérgio [UNESP]; Caputo, Fabrizio; Greco, Camila Coelho [UNESP] (Elsevier, 2018)
Rapid force capacity, identified by rate of rise in contractile force at the onset of contraction, i.e., the rate of force development (RFD), has been considered an important neuromuscular parameter of physical fitness in elderly individuals. Randomized control studies conducted in adults have found that resistance training may elicit different outcomes in terms of RFD and muscle strength. Thus, the main purpose of this study was to review systematically the literature for studies regarding the influence of resistance training on muscle strength and RFD in elderly persons. A literature search was performed in major electronic databases from inception to March 2017. Studies including health individuals with a mean age ≥ 60 years, describing the effect of resistance training on RFD and muscle strength were found eligible. The outcomes were calculated as the difference in percentage change between control and experimental groups (% change) and data were presented as mean ± 95% confidence limits. Meta-analyses were performed using a random-effects model and, in addition, simple and multiple meta-regression analyses were used to identify effects of age, training type, sessions per week and training duration on % change in RFD and muscle strength. Thirteen training effects were collected from 10 studies included in the meta-analysis. The resistance training program had a moderate beneficial effect on both muscle strength (% change = 18.40%, 95% CL 13.69 – 23.30, p < 0.001) and RFD (% change = 26.68, 95% CL 14.41–35.52, p < 0.001). Results of the meta-regression revealed that the variables age, training type (i.e., strength and explosive), training duration (4–16 weeks) and sessions per week had no significant effects on muscle strength and RFD improvement. Moreover, there was no significant relationship (p = 0.073) between the changes in muscle strength and RFD. It can be concluded that explosive training and heavy strength training are effective resistance training methods aiming to improve both muscle strength and RFD after short-to-medium training period. However, muscle strength and RFD seem to adapt differently to resistance training programs, suggesting caution for their interchangeable use in clinical assessments of the elderly.
Keywords: Aging; Elderly; Explosive training; Resistance training